Direct Molecular Diagnosis of Aspergillosis and CYP51A Profiling from Respiratory Samples of French Patients - Zhao, Yanan; Garnaud, Cécile; Brenier-Pinchart, Marie-Pierre; Thiébaut-Bertrand, Anne; Saint-Raymond, Christel; Camara, Boubou; Hamidfar, Rebecca; Cognet, Odile; Maubon, Danièle; Cornet, Muriel; Perlin, David S. (Frontiers in Microbiology, 2016)
Background: Microbiological diagnosis of aspergillosis and triazole resistance is limited by poor culture yield. To better estimate this shortcoming, we compared culture and molecular detection of A. fumigatus in respiratory samples from French patients at risk for aspergillosis. Methods: A total of 97 respiratory samples including bronchoalveolar lavages (BAL), bronchial aspirates (BA), tracheal aspirates, sputa, pleural fluids, and lung biopsy were collected from 33 patients having invasive aspergillosis (n=12), chronic pulmonary aspergillosis (n=3), allergic bronchopulmonary aspergillosis (n=7) or colonization (n=11) and 28 controls. Each specimen was evaluated by culture, pan-Aspergillus qPCR, and CYP51A PCR and sequencing. Results: One A. flavus and 19 A. fumigatus with one multiazole resistant strain (5.3%) were cultured from 20 samples. Culture positivity was 62.5%, 75%, 42.9%, and 15.8% in ABPA, CPA, IA and colonized patients, respectively. Aspergillus detection rate was significantly higher by pan-Aspergillus qPCR than by culture in IA (90.5% vs 42.9%; P<0.05) and colonization group (73.7% vs 15.8%; P<0.05). The CYP51A PCR found one TR34/L98H along with 5 novel cyp51A mutations (4 non-synonymous and 1 promoter mutations), yet no association can be established currently between these novel mutations and azole resistance. The analysis of 11 matched pairs of BA and BAL samples found that 9/11 BA carried greater fungal load than BAL and CYP51A detection was more sensitive in BA than in BAL. Conclusion: Direct molecular detection of Aspergillus spp. and azole resistance markers are useful adjunct tools for comprehensive aspergillosis diagnosis. The observed superior diagnostic value of BAs to BAL fluids warrants more in-depth study.